2019
DOI: 10.1161/jaha.118.010995
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Maternal Heat Exposure During Early Pregnancy and the Associated Congenital Heart Defect Burden in the United States

Abstract: Background More intense and longer‐lasting heat events are expected in the United States as a consequence of climate change. This study aimed to project the potential changes in maternal heat exposure during early pregnancy (3–8 weeks post conception) and the associated burden of congenital heart defects ( CHD s) in the future. Methods and Results This study expanded on a prior nationwide case‐control study that evaluated the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 38 publications
0
55
0
Order By: Relevance
“…Several epidemiological studies over the past five years have reported associations between high temperatures and adverse pregnancy outcomes, including preterm birth, stillbirth, and low birth weight (LBW),3 , 4 as well as congenital heart defects 5. (At least two studies have also examined ambient temperature in relation to neural tube defects 6 , 7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies over the past five years have reported associations between high temperatures and adverse pregnancy outcomes, including preterm birth, stillbirth, and low birth weight (LBW),3 , 4 as well as congenital heart defects 5. (At least two studies have also examined ambient temperature in relation to neural tube defects 6 , 7…”
mentioning
confidence: 99%
“…Animal studies suggest that heat exposure during early pregnancy could interfere with normal protein synthesis through the production of heat-shock proteins 11. Disrupting protein homeostasis could lead to fetal cell damage, potentially altering fetal development 5. Previous research in the general (nonpregnant) population shows that circulating levels of markers of inflammation and oxidative stress are associated with ambient temperatures 12 , 13 , 14 , 15.…”
mentioning
confidence: 99%
“…Using a stringent analytic approach, 5% of birth defects were associated with season of conception. Because previous studies have focused on more common birth defects, such as cleft lip and palate, cardiac anomalies, and neural tube defects (NTDs), scant data are available for many anomalies [ 12 , 19 , 20 , 21 ]. Our findings provide evidence of increased prevalence of several such birth defects among offspring conceived in the summer relative to the winter.…”
Section: Discussionmentioning
confidence: 99%
“…High temperatures can increase ozone concentrations and trap pollutants closer to the ground [ 26 ]. Animal studies indicate that maternal heat exposure during early pregnancy may induce fetal cell death or malformations [ 19 , 27 ]. In support of this, Lin et al found increased odds of congenital heart disease for offspring of women who experienced more frequent or longer lasting extreme heat events during the spring or summer [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial epidemiological evidence associates the sustained presence of adverse healthy lifestyle factors with increased risk of CHD mortality 4 . However, few studies have been done to predict the risk of individual congenital malformations, including CHD 5 .…”
Section: Introductionmentioning
confidence: 99%